2019
DOI: 10.1002/jcp.28249
|View full text |Cite
|
Sign up to set email alerts
|

Complexity on modulation of NF‐κB pathways by hepatitis B and C: A double‐edged sword in hepatocarcinogenesis

Abstract: Nuclear factor‐κB (NF‐κB), a family of master regulated dimeric transcription factors, signaling transduction pathways are active players in the cell signaling that control vital cellular processes, including cell growth, proliferation, differentiation, apoptosis, morphogenesis, angiogenesis, and immune responses. Nevertheless, aberrant regulation of the NF‐κB signaling pathways has been associated with a significant number of human cancers. In fact, NF‐κB acts as a double‐edged sword in the vital cellular pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 111 publications
(162 reference statements)
1
19
0
Order By: Relevance
“…IKBKB, CHUK, and NFKBIA are important genes in the NF-κB pathway that are involved in regulating various proteins involved in physiological and pathological processes such as inflammatory translation, immunity, cell proliferation, differentiation, and apoptosis. If NF-κB is overactivated, it will cause immune liver damage and promote the development of liver fibrosis by inhibiting apoptosis of hepatic stellate cells [48]. This study indicated that IKBKB is regulated by the MOL000422 compound, which acts on 11 pathways.…”
Section: Discussionmentioning
confidence: 75%
“…IKBKB, CHUK, and NFKBIA are important genes in the NF-κB pathway that are involved in regulating various proteins involved in physiological and pathological processes such as inflammatory translation, immunity, cell proliferation, differentiation, and apoptosis. If NF-κB is overactivated, it will cause immune liver damage and promote the development of liver fibrosis by inhibiting apoptosis of hepatic stellate cells [48]. This study indicated that IKBKB is regulated by the MOL000422 compound, which acts on 11 pathways.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, these viruses can contribute to the oncogenic state either through chronic NF-κB-dependent inflammation or by the sustained activity of viral activators of NF-κB. Examples of virally encoded NF-κB activators include the LMP1 protein of Epstein–Barr virus (B cell lymphoma, nasopharyngeal carcinoma) [ 64 ], the vFLIP protein of Kaposi sarcoma herpesvirus (sarcoma, lymphoma) [ 64 ], the Tax protein of HTLV-1 (T cell leukemia) [ 65 ], the X protein of hepatitis B virus (liver cancer) [ 66 ], and the E6 and E7 proteins of some strains of the human papillomavirus (cervical cancer) [ 67 ].…”
Section: Cancer Cell-induced Activation Of Nf-κbmentioning
confidence: 99%
“…Apart from the direct HBV-dependent induction of ROS i.e by HBx, there are indirect mechanisms. Both regulatory proteins of HBV (HBx and LHBs) have the capacity to activate NF-kB [268,300,301,302]. On the one hand, the HBV-dependent activation of NF-kB leads to the induction of proinflammatory cytokines like TNFα, lymphotoxin-α or IL-6 and on the other hand HBx was described to suppress the expression of anti-inflammatory cytokines [302,303,304,305,306].…”
Section: Ros Nrf2 and The Virus-associated Pathogenesismentioning
confidence: 99%